2011
DOI: 10.4236/ojs.2011.12006
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Estimations for Generalized RayleighDistribution under Progressively Type-I IntervalCensored Data

Abstract: In this paper, inference on parameter estimation of the generalized Rayleigh distribution are investigated for progressively type-I interval censored samples. The estimators of distribution parameters via maximum likelihood, moment method and probability plot are derived, and their performance are compared based on simulation results in terms of the mean squared error and bias. A case application of plasma cell myeloma data is used for illustrating the proposed estimation methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In this work, the author analyzed a one-parameter exponential distribution under this censoring, and obtained classical estimates for the unknown parameter. Statistical inference under progressive type-I interval censoring has been further discussed by Ashour and Afify (2007) for exponentiated Weibull family, Ng and Wang (2009) for Weibull distribution, Lio et al (2011) for generalized Rayleigh distribution, Xiuyun and Zaizai (2011) for gamma distribution and Chen and Lio (2010) and Chen et al (2013) for generalized exponential distribution. Bayesian inference under this censoring has also been discussed by various researchers, see for instance, Lin and Lio (2012) for Weibull and generalized exponential distributions, Peng and Yan (2013) for generalized exponential distribution and Pradhan and Gijo (2013) for lognormal distribution.…”
Section: Introductionmentioning
confidence: 98%
“…In this work, the author analyzed a one-parameter exponential distribution under this censoring, and obtained classical estimates for the unknown parameter. Statistical inference under progressive type-I interval censoring has been further discussed by Ashour and Afify (2007) for exponentiated Weibull family, Ng and Wang (2009) for Weibull distribution, Lio et al (2011) for generalized Rayleigh distribution, Xiuyun and Zaizai (2011) for gamma distribution and Chen and Lio (2010) and Chen et al (2013) for generalized exponential distribution. Bayesian inference under this censoring has also been discussed by various researchers, see for instance, Lin and Lio (2012) for Weibull and generalized exponential distributions, Peng and Yan (2013) for generalized exponential distribution and Pradhan and Gijo (2013) for lognormal distribution.…”
Section: Introductionmentioning
confidence: 98%
“…If q= 1, the GRD reduces to the traditional Rayleigh distribution. As indicated by [2][3][4][5], the GRD has been studied in many papers. Also, Surles and Padgett [6] showed that the two-parameter GRD can be used quite effectively in modeling strength data and also modeling general lifetime data.…”
mentioning
confidence: 99%
“…In 2001, two parameter Burr Type X distribution was introduced by Surles and Padgett [14]. Abdel-Hady [1], Kundu and Raqab [8] and Lio, Chen and Tsai [9] prefer to call this distribution GRD; this name will be adopted in this work. For α>0 and λ>0, the two-parameter GRD will be denoted by GRD(α, λ) and its cumulative distribution function is given by:…”
Section: Introductionmentioning
confidence: 99%
“…It is used as a model for wind speed and is often applied to wind driven electrical generation. It can also be used in modelling strength and lifetime data (we refer an interested reader to, Kundu & Raqab [8], Lio, Chen and Tsai [9], Samaila and Cenac [13] and Surles and Padgett [14]). The graph of the GRD is shown in figure 1 for different shape parameter values.…”
Section: Introductionmentioning
confidence: 99%